(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Human Resources (HR) professionals in the healthcare industry play a vital role in managing the workforce that is essential for delivering quality patient care. However, they encounter unique challenges not commonly faced by HR professionals in other industries. This paper explores the specific difficulties such as talent acquisition, employee retention, compliance with regulations, staff burnout, and the integration of technology. Understanding these challenges can help HR professionals implement effective strategies tailored to the specific needs of the healthcare sector. Human Resource (HR) professionals in the healthcare industry face unique challenges due to the sector's dynamic and high-pressure environment. Unlike other industries, healthcare HR must manage workforce shortages, high turnover rates, regulatory compliance, and employee burnout while ensuring quality patient care. The complexity of healthcare staffing, including the need for specialized skills and continuous training, adds to the difficulty of recruitment and retention. Additionally, HR professionals must navigate ethical concerns, labor laws, and evolving healthcare policies to maintain a stable workforce. This paper explores the critical challenges faced by HR professionals in healthcare, the impact of these challenges on organizational efficiency, and strategies to mitigate workforce-related issues. By addressing these concerns, healthcare organizations can enhance employee satisfaction, improve patient outcomes, and create a more sustainable work environment.